IM4Equity: an implementation science meta-framework for community-engaged partnerships to advance health equity - Perez, Lilian G.; Merle, James L.; Smith, Justin D.; Dopp, Alex R.; Huebschmann, Amy G. (BMC health services research, 2025)
Background Implementation determinant frameworks identify factors that may impede or facilitate implementation of evidence-based innovations (EBI) in new contexts, including diverse community settings. For health equity initiatives, variations in which frameworks are used make synthesis and identification of shared determinants difficult, including equity constructs. Further, such frameworks are rarely informed by community partner input. We describe the development of an equity-centered meta-framework that centers community-engagement called IM4Equity (Crosswalk of 4 IMplementation Frameworks to advance health Equity) as part of the Disparities Elimination through Coordinated Interventions to Prevent and Control Heart and Lung Disease Risk (DECIPHeR) Alliance, comprised of seven research-community partnerships across the U.S. Methods We conducted a crosswalk of determinants (domains and constructs within domains) from the Exploration, Preparation, Implementation, and Sustainment framework; Practical, Robust Implementation and Sustainability Model; updated Consolidated Framework for Implementation Research; and Health Equity Implementation Framework. We reviewed original source publications and resources to identify determinants from each framework, which informed a prototype figure. We obtained feedback on the figure with a user-centered design approach with DECIPHeR research teams and community partners, plus framework developers. We used thematic analysis to summarize the feedback and inform iterative development of supporting materials to guide community partner engagement in informing and applying IM4Equity (e.g., blank framework template, guidance for completing the template). Results IM4Equity identifies shared and unique domains: intra- and extra-organizational contexts, characteristics of individuals involved in implementation, innovation characteristics, bridging factors, implementation process, and implementation phases. We identified examples of shared constructs for each domain and example factors that may improve health equity or maintain systems of oppression (e.g., structural racism). Feedback sessions identified two areas for improving the usability of IM4Equity, which we addressed in the final figure and supporting materials: 1) design and appropriateness (e.g., language) and 2) approach for integrating community partner perspectives. Conclusions IM4Equity highlights key overlapping determinants across existing frameworks, which can promote shared learning across health equity initiatives. IM4Equity is one of the first meta-frameworks to promote co-creation and application of an implementation framework with community partners, which may help inform more equitable implementation measures and strategies to advance health equity.